Unravelling the conductance path through single-porphyrin junctions. Issue 36 (13th August 2019) - El Abbassi, Maria; Zwick, Patrick; Rates, Alfredo; Stefani, Davide; Prescimone, Alessandro; Mayor, Marcel; van der Zant, Herre S. J.; Dulić, Diana
Abstract : By studying transport through seven structurally related porphyrin derivatives with a machine learning algorithm we could identify and distinguish three different electronic paths. Abstract : Porphyrin derivatives are key components in natural machinery enabling us to store sunlight as chemical energy. In spite of their prominent role in cascades separating electrical charges and their potential as sensitizers in molecular devices, reports concerning their electronic transport characteristics are inconsistent. Here we report a systematic investigation of electronic transport paths through single porphyrin junctions. The transport through seven structurally related porphyrin derivatives was repeatedly measured in an automatized mechanically controlled break-junction set-up and the recorded data were analyzed by an unsupervised clustering algorithm. The correlation between the appearances of similar clusters in particular sub-sets of the porphyrins with a common structural motif allowed us to assign the corresponding current path. The small series of model porphyrins allowed us to identify and distinguish three different electronic paths covering more than four orders of magnitude in conductance.